Kohesi Gramatikal dalam Tajuk Rencana Surat Kabar Riau Pos - Anggraini, Siska; Asnawi, Asnawi (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
The research objectives are 1) To describe and analyze the use of reference grammatical cohesion in the editorial of the Riau Pos newspaper. 2) To describe and analyze the use of subsitutional grammatical cohesion in the editorial of the Riau Pos newspaper. 3) To describe and analyze the use of grammatical cohesion of conjunctions in the editorial of the Riau Pos newspaper. The research method is a qualitative type of phenomology. The theory used is Darma (2014), Djajasudarma (2010), Charlina dan Sinaga (2006). The data source for this research is the Riau Pos newspaper edition 1 to 28 February 2021. Hermeneutic data collection techniques are collecting, grouping, interpreting, concluding. The result of grammatical cohesion research in the editorial of the Riau Pos newspaper found reference related to pronouns found as many as 57 data, substitusions found 14 data, conjunctions found 94 data